Konsep bertaklid dalam islam - Mahyuddin Abu Bakar,; Azman Md Zain, (Universiti Kebangsaan Malaysia, 2005)
Islamic jurispudence recognizes the practices of taqlid in school of Hanafi, Maliki, Syafi’e and Hanbali. It is because most of Muslim do not have the ability and capability for ijtihad, hence taqlid is the best for them to perform as ibadah. Actually, the understanding (tasamuh) of taqlid is to avoid the fanatics in each schools that eventually can break the unity of ummah..Moreover Muslim should be aware of this concept and they are not allowed to practice the taqlid in aqidah. Earnling knowledge in aqidah is the responsibility for each Muslim because there is strong relationship with the faith. The faith must build based on understanding. Therefore, the scholars have taken an approach to give the permissibility of taqlid in feqh, with the stands of adab and akhlak